Impact of Tacrolimus Compared With Cyclosporin on the Incidence of Acute Allograft Rejection in Human Immunodeficiency Virus–Positive Kidney Transplant Recipients. Issue 4 (April 2016) - Gathogo, Esther; Harber, Mark; Bhagani, Sanjay; Levy, Jeremy; Jones, Rachael; Hilton, Rachel; Davies, Graham; Post, Frank A
Abstract : Background: Kidney transplantation (KT) of human immunodeficiency virus (HIV)–positive patients has transformed the management of end-stage kidney disease in this population. Although favourable outcomes have been reported, patients experience high rates of acute allograft rejection (AR). We examined factors associated with AR in the first year after KT, with particular emphasis on the choice of calcineurin inhibitor (CNI) immunosuppressive therapy. Methods: We conducted a national observational cohort study of HIV/KT in the United Kingdom. Patients were included if HIV positive at KT, transplanted in the United Kingdom between January 2005 and December 2013, and did not experience primary graft failure. Kaplan-Meier methods were used to estimate host/graft survival and cumulative incidence of biopsy proven AR. Logrank tests were used to compare survival, and Cox proportional hazard models to examine factors associated with AR. Results: Our study analyzed the incidence of AR in the first year after KT in 78 HIV-positive patients of whom 31 initiated cyclosporin (CsA) and 47 tacrolimus (Tac) based immunosuppression. AR was observed in 28 patients (36%) after a median of 2.6 (interquartile range, 0.5-5.9) months. The cumulative incidence of AR at 1 year was 58% and 21% among patients on CsA and Tac, respectively ( P =0.003). Choice of CNI was the only factor significantly associated with AR (hazard ratio for Tac vs CsA 0.25 [95% confidence interval, 0.11-0.57], P = 0.001). Subtherapeutic CNI concentrations were common in the first 12 weeks after KT. Conclusions: Our data suggest that Tac may be the preferred CNI for use in KT in people living with HIV. Abstract : This small observational cohort study describes the difficulties of using calcineurin inhibitors in HIV-positive kidney transplant recipients, suggesting that tacrolimus use may be preferred because it was independently associated with lower incidence of acute rejection during the first year after transplant. Supplemental digital content is available in the text.